HUBUNGAN ANTARA MATHEMATICS ANXIETY DAN WORKING MEMORY CAPACITY PADA SISWA SMP NEGERI 4 SINGKAWANG - Salvani, Ria; Ade Mirza; Munaldus (Universitas Tanjungpura, 2026)
Mathematics anxiety is an affective factor that can negatively influence students’ learning in mathematics. High levels of anxiety may disrupt cognitive functioning, particularly working memory, which is essential for processing and solving mathematical problems. This issue is important at the junior high school level, where academic and emotional demands increase. This study aimed to investigate the relationship between mathematics anxiety and working memory capacity among students at SMP Negeri 4 Singkawang. The research employed a quantitative correlational design involving Grade VIII students. Data were collected through a mathematics anxiety questionnaire and working memory capacity tasks consisting of digit span task and operation span task. Data were analyzed using descriptive statistics and Pearson correlation analysis. The results show that students generally experience moderate levels of mathematics anxiety and working memory capacity. The analysis also reveals a significant negative relationship between mathematics anxiety and working memory capacity, with higher anxiety associated with lower working memory capacity. In conclusion, mathematics anxiety is negatively related to working memory capacity.